In-vitro Antimicrobial Analysis of the Fumes Originates by Chandrodaya Varti (Agnikarma) in Cervical Cell Pathology - Nisha Chaudhary; Anjali Verma; Ajay Kumar Gupta; Khem Chand Sharma (AYUSHDHARA, 2024)
Woman’s health is incredibly valuable and crucial component of a healthy country. There are so many diseases that affects quality of life of women, cervical cell pathology is one of them. On the basis of etiopathogenesis, sign, and symptoms and previous scientific studies it can be correlated with Garbhashaya Griva Mukhagata Vrana. Here we have proved the antimicrobial activity of Chandrodaya Varti by fumes originating from it with the help of in vitro study on different strain of bacteria and fungi and due to antimicrobial properties present in the fumes of Chandrodaya Varti. It kills the microorganisms of cervical cell pathology and due to Sooksham, Laghu, Vishada properties of fumes it regenerates new cell tissue in Garbhashaya Griva mukha. The present study highlights the effect of fumes originating (fumigation) from Chandrodaya varti in the management of Garbhashaya Griva Mukhgata Vrana.